P2X7 Interactions and Signaling – Making Head or Tail of It - Kopp, Robin; Krautloher, Anna; Ramírez-Fernández, Antonio; Nicke, Annette (Frontiers in Molecular Neuroscience, 2019)
Extracellular adenine nucleotides play important roles in cell-cell communication and tissue homeostasis. High concentrations of extracellular ATP released by dying cells are sensed as a danger signal by the P2X7 receptor, a non-specific cation channel. Studies in P2X7 knockout mice and numerous disease models have demonstrated an important role of this receptor in inflammatory processes. P2X7 activation has been shown to induce a variety of cellular responses that are not usually associated with ion channel function, for example changes in the plasma membrane composition and morphology, ectodomain shedding, activation of lipases, kinases, and transcription factors, as well as cytokine release and apoptosis. In contrast to all other P2X family members, the P2X7 receptor contains a long intracellular C-terminus that constitutes 40% of the whole protein and is considered essential for most of these effects. So far, over 50 different proteins have been identified to physically interact with the P2X7 receptor. However, few of these interactions have been confirmed in independent studies and for the majority of these proteins, the interaction domains and the physiological consequences of the interactions are only poorly described. Also, while the structure of the P2X7 extracellular domain has recently been resolved, information about the organisation and structure of its C-terminal tail remains elusive. After shortly describing the structure and assembly of the P2X7 receptor, this review gives an update of the identified or proposed interaction domains within the P2X7 C-terminus, describes signalling pathways in which this receptor has been involved, and provides an overlook of the identified interaction partners.